UHF front‐end feeding RFID‐based body sensor networks by exploiting the reader signal. Issue 5 (19th May 2016) - Pasca, M.; Colella, R.; Catarinucci, L.; Tarricone, L.; D'Amico, S.; Baschirotto, A.
Abstract: This paper presents an integrated, high‐sensitivity UHF radio frequency identification (RFID) power management circuit for body sensor network applications. The circuit consists of a two‐stage RF‐DC Dickson's rectifier followed by an integrated five‐stage DC‐DC Pelliconi's charge pump driven by an ultralow start‐up voltage LC oscillator. The DC‐DC charge pump interposed between the RF‐DC rectifier and the output load provides the RF to load isolation avoiding losses due to the diodes reverse saturation current. The RF‐DC rectifier has been realized on FR4 substrate, while the charge pump and the oscillator have been realized in 180 nm complementary metal oxide semiconductor (CMOS) technology. Outdoor measurements demonstrate the ability of the power management circuit to provide 400 mV output voltage at 14 m distance from the UHF reader, in correspondence of −25 dBm input signal power. As demonstrated in the literature, such output voltage level is suitable to supply body sensor network nodes. Key Points: A power management circuit suitable to power body sensor network nodes exploiting the energy from a UHF reader is presented It is made by an initial RF‐DC rectifier followed by a charge pump that allows to isolate the output load from the input RF source Indoor and outdoor measurements have been performed in order to validate the presented mathematical model of the circuit